British children's fiction in the Second World War [ - Edwards, Owen Dudley (Edinburgh : Edinburgh University Press, 2007)
A broad-ranging discussion of wartime children's literature and its effects. Covering over 100 writers, this work looks at the literary inheritance when the war broke out and asks whether children's
1. Pt. 1. The school of war. Orwell v. Richards: children's fiction to 1940 -- 2. Rations and quislings -- 3. Evacuees and gurus -- 4. Women and fathers -- 5. Officials and genteel-men -- 6. pt. 2. Lessons which may have been learned. God's things and others' -- 7. Identity authority and imagination -- 8. Gender -- 9. Class -- 10. Race
Includes bibliographical references and index
Keywords: Children -- Books and reading -- Great Britain -- History -- 20th century; World War, 1939-1945 -- Social aspects -- Great Britain